Rating Evaluation of the Activities of the Authorities of the Constituent Entities of the Russian Federation to Preserve and Support the Native Languages of the Peoples of the Russian Federation - A. A. Maltseva; N. E. Barsukova; E. V. Klyushnikova (Управленческое консультирование)
The article is devoted to the state and development of language policy at the regional level. Taking into account the federal structure of the country and a high degree of language and ethnic diversity in the Russian regions there are significant differences in the organizational and substantive aspects of language policy, key principles and directions which are formulated at the federal level.The paper presents the methodological basis and practical implementation of the rating assessment of the activities of the authorities of the subjects of the Russian Federation to preserve and support the native languages of the nations of the Russian Federation. The aim of the work is to develop and test a system of indicators characterizing the level of regional language policy. The key research methods were analysis, comparison, standardization, ranking.On the purposes of the study, analytical indicators were identified, which are available in the public domain on the official websites of state bodies and a number of other structures. Indicators are characterized by both quantitative and qualitative assessment. In terms of content, they were divided into 4 thematic clusters: tools for the implementation of state national policy in the region, including support, preservation and study of native languages of the nations of the Russian Federation; preservation and study of native languages in the field of education and science; preservation and study of native languages in the field of culture and art; preservation and study of native languages in the mass media.Due to significant differences between the regions of the Russian Federation in terms of language diversity, they were divided into 4 groups, which values of individual indicators, as well as the integral index and sub-indices were studied. In order to ensure data comparability, the procedure of data standardization is proposed in the methodology. As a result of the study, the assessment of individual indicators was carried out and the ranking of the subjects of the Russian Federation within each classification group was carried out according to the level of development of regional language policy. As a result, the leading regions (the Republic of Tatarstan, KhantyMansi Autonomous Area — Ugra, Ulyanovsk region) were identified, which can be considered benchmarks for other subjects of the Russian Federation of the corresponding classification group.